Single Nucleotide Polymorphisms associated with alimentary fatty liver disease are not genetic risk factors for treatment-associated hepatic steatosis in HIV patients on HAART - Leona Dold; Cordula Berger; Carolin Luda; Christoph Boesecke; Carolynne Schwarze-Zander; Hans-Dieter Nischalke; Jan-Christian Wasmuth; Jürgen Kurt Rockstroh; Ulrich Spengler (Journal of Clinical Research In HIV AIDS And Prevention, 2013)
Analyzing SNPs linked to fatty liver disease, this study finds no association with HAART‑related hepatic steatosis in HIV patients. The work underscores the multifactorial nature of antiretroviral toxicity and points to metabolic and pharmacologic contributors beyond common variants.
Keywords: HIV